Sensitivity of transpiration to influencing factors at varying drought levels in Schima superba - Zhao, Xiaowei; Zhu, Liwei (Frontiers in Forests and Global Change, 2025)
IntroductionUneven rainfall distribution alters tree water use patterns, ultimately influencing plantation establishment.MethodsBased on monthly rainfall, six drought levels were classified. Whole-tree sap flux and meteorological variables were monitored across these levels from 2010 to 2013 in a pure Schima superba plantation in South China. The relationships between daily transpiration (Tt) and the influencing factors were modeled using the Support vector regression (SVR) method. Shapley additive explanations (SHAP) values were employed to characterize the sensitivity and contributions of four environmental variables to Tt.ResultsThe results indicate that monthly rainfall (RFt) significantly influences the sensitivity of these four environmental variables to Tt when RFt exceeds 300 mm (Level 6). Furthermore, when RFt is 300 mm or less (Levels 1–5), the sensitivity of these factors and their total contributions to Tt are independent of tree size.DiscussionOur findings indicate that the decoupling between Tt and environmental factors may be a significant characteristic of ongoing water stress during high rainfall months. Additionally, these findings enhance the predictive capability of machine learning models in assessing tree water use.